Determining industries' environmental training needs, with special reference to the manufacturing and engineering industries in the Eastern Cape - Mabunda, Khensani (Rhodes University, Faculty of Education, Department of Education, 1998)
This paper presents the outcome of two case studies and a survey of manufacturing and engineering industries in the Eastern Cape, to explain their environmental education and / or training needs. The methods involved in case studies were interviews, observation and document analysis and for the survey a postal questionnaire. Respondents were generally able to identify their companies' environmental impacts and most thought that education and/training has a role to play in helping them deal with those impacts. While respondents identified environmental awareness for workers as the main role that education and / or training can play, it also has to help management understand its environmental role in dealing with environmental management systems and legislation, as well as supporting education and training. Education and/or training should take both managers and workers beyond the superficial understanding of the concept of environment. In-house and external trainers were identified as potential trainers as this would both overcome a current lack of capacity and make continuity possible when external trainers cease training. Trainers should be environmentally qualified. Respondents have mostly shown support for learning-on-the-job but less so on special environmental courses or including an environmental component in all training programmes. Some training sections consider their sections as already overladen and unable to accommodate other training programmes. The problem is therefore more logistic than environmental.
Keywords: Manufacturing industries -- Employees -- Training of -- South Africa -- Eastern Cape; Environmental education -- South Africa -- Eastern Cape